Possibilities to implement pinch analysis in the steel industry - Case study at SSAB Strip Products in Luleå - Isaksson, Johan; Harvey, Simon (2010)
Steelmaking is a highly energy intensive industry but has during the past years done a lot to make the processes more efficient. Both concern for the environment and more expensive energy have resulted in this development. More modern and better technology has caused the biggest leaps towards more energy efficient processes, but during the past years also the concept of process integration has come to play an important role. Studies have been made on energy and exergy flows and mathematical programming has been used to create models of the dynamics of the energy and material flows in steelmaking processes. So far only a few smaller pinch targeting studies have been made on this type of industry, and only on smaller sub-systems. Based on experience about pinch analysis and the nature of the steelmaking process, there is now a wish to evaluate this technique for larger, interconnected systems. For that purpose a pinch targeting study was made at SSAB Strip Products in Luleå.Pinch analysis was originally developed for large systems with many streams. The streams should preferably also be possible to heat exchange. This makes implementation in the steel industry somewhat restricted as there are relatively few streams, and the ones with the largest energy content are in the form of molten metal, hot slag or as radiation from slabs. Potential for energy recovery from such streams has been evaluated in previous studies and will not be treated here.The study shows that pinch analysis is a powerful tool to graphically visualize the potential for energy recovery in the coking plant area, including the gas cleaning system. A relatively large amount of streams with demand for heating or cooling contribute a quite complex network which is hard to grasp without a systematic tool like pinch analysis. This preliminary study shows that there are several unutilized high temperature excess heat streams, which together can replace the local steam boiler.In the rest of the process however, demand for heat is located only at high ...